Subgroup analysis of imaging scans, invasive examinations and prognosis in mild-to-moderate isolated foetal cerebral ventriculomegaly: a retrospective study in China - Chun Yang; Xia Chi; Yan Wang; Cuiping Zhang; Ran Zhou; Xuemei Jia; Fengchang Qiao; Zhengfeng Xu (Journal of International Medical Research)
Objective This study aimed to analyse the causes of foetal mild-to-moderate isolated ventriculomegaly (IVM) and to evaluate the prognosis of neurological development in surviving children in different subgroups. Methods We retrospectively studied mild-to-moderate IVM diagnosed by prenatal ultrasound scans in different subgroups according to the laterality of IVM, the degree of IVM and foetal sex independently. The results of foetal chromosomal microarray analysis, virological tests of umbilical cord blood or amniotic fluid, foetal magnetic resonance imaging and ultrasound were collected. Long-term follow-up was performed to assess the neurodevelopment of children within 66 months through telephone interviews and/or the Ages and Stages Questionnaire-3. Results The moderate group showed more chromosomal abnormalities (16.2% vs. 4.1%) and greater structural anomalies in the brain (31.8% vs. 7.5%) than the mild group. Female foetuses showed more structural anomalies than male foetuses (25.0% vs. 7.2%). However, an adverse prognosis of children was not different across the different subgroups. Conclusion Moderate IVM may be more strongly associated with chromosomal aberrations and structural malformations than mild IVM. However, the adverse prognosis of children was similar between the different subgroups analysed.